PENGARUH POLA PEMBAYARAN ANGSURAN DAN PENGAWASAN PEMBIAYAAN MURABAHAH TERHADAP LABA USAHA PEDAGANG KECIL (Penelitian pada Koperasi Jasa keuangan Syariah BMT El-Tazkiyah Bandung) - Nurrohman Syarif (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
ABSTRACK This article describes the effect of installment payment and supervision patterns on murabahah financing on the profit of small traders in the Islamic Financial Services Cooperative BMT El-Tazkiyah Bandung. In this research the method used is descriptive analytic method with survey techniques. The survey was conducted by taking a sample from the population and using a questionnaire as a measurement tool for data. Descriptive method is used to describe the results of the analysis of the pattern of murabahah financing installments made by traders and financial supervision conducted by management. The installment pattern is a pattern of repayment of principal loans from members to Sharia cooperatives carried out in three ways namely daily, weekly, or monthly repayments. This pattern is thought to affect their business profits due to the capital cycle used. In addition to the choice of installment payment patterns, what influences the addition of financing is financing supervision conducted by BMT management itself. As an institution that is in direct contact with the capital requirements of small traders, management efforts in the selection of installment payment patterns and financing supervision should not only be in the interests of profitability and security of the BMT, but can also increase the profitability of small traders.